Respuesta :
The tree increased its height by 19.44%
(43 - 36) ÷ 36 = 7 ÷ 36 = 0.1944 * 100% = 19.44%
36 is the basis of the equation. It is the 100%
7 is the increase in height (inches). It is the 19.44%
43 is the total height. It is 119.44% height of the tree.
Whatever height the tree grow to, if the question is percentage since it was planted, then 36 inches is the basis.
If the problem refers to the height increase based on the latest height measurement, then 43 inches is the basis.
If the 7 inches increase in height is constant every year. Then, an equation will show:
y = 36 + 7x
where y is the total growth through the years. 36 is the initial height, 7 is the constant rate of growth, and x is the number of years the tree has grown.
(43 - 36) ÷ 36 = 7 ÷ 36 = 0.1944 * 100% = 19.44%
36 is the basis of the equation. It is the 100%
7 is the increase in height (inches). It is the 19.44%
43 is the total height. It is 119.44% height of the tree.
Whatever height the tree grow to, if the question is percentage since it was planted, then 36 inches is the basis.
If the problem refers to the height increase based on the latest height measurement, then 43 inches is the basis.
If the 7 inches increase in height is constant every year. Then, an equation will show:
y = 36 + 7x
where y is the total growth through the years. 36 is the initial height, 7 is the constant rate of growth, and x is the number of years the tree has grown.
Answer: [tex]\dfrac{7}{36}\times 100=19.44\%[/tex] is the required expression.
Step-by-step explanation:
Since we have given that
Length of tree initially = 36 inches
Length of tree after one year = 43 inches
We need to find the percentage of increase in the tree's height.
So, expression would be
[tex]\dfrac{Difference}{Original}\times 100\\\\=\dfrac{43-36}{36}\times 100\\\\=\dfrac{7}{36}\times 100\\\\=19.44\%[/tex]
Hence, [tex]\dfrac{7}{36}\times 100=19.44\%[/tex] is the required expression.